Investigation of Polymorphic Variants of PPARD and APOE Genes in Turkish Coronary Heart Disease Patients - (:unkn) unknown (MARY ANN LIEBERT, INC, 2012)
The aim of this study was to determine the role of polymorphic variants of apolipoprotein E (APOE) and peroxisome proliferator-activated receptor delta (PPARD) genes in the development of coronary heart disease (CHD), and the PPARD and APOE gene-gene interaction in a Turkish population. This study was carried out using a sample of 223 patients with CHD (103 with diabetes and 120 without diabetes) and 101 controls. PPARD + 294T/C and APOE genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism technique. The PPARD and APOE genotype distributions were the same between study groups (p > 0.05). In the nondiabetic CHD patients, the PPARD + 294 C allele showed higher serum low-density lipoprotein cholesterol (LDL-C) level than the common + 294 TT homozygote genotype (3.83 +/- 1.01 vs. 3.33 +/- 1.14, p = 0.015). In addition, a significant association between APOE 4 and PPARD + 294 C alleles was detected based on their effects on LDL-C in the nondiabetic CHD patients (+ 294 C/APOE4: 4.43 +/- 0.88 vs. + 294 TT/nonAPOE 4: 3.48 +/- 1.09, p = 0.009). This association indicated the interaction of two genes on plasma LDL-C levels ascended in the order + 294 T< + 294 T-APOE 4< + 294 C< APOE 4< + 294 C-APOE 4. The PPARD + 294 C allele was associated with higher incidence of left ventricular hypertrophy (LVH) in all male patients with body mass index > 27. In addition, the CHD patients who were + 294 C allele carriers had a 2.48-fold higher risk of LVH than subjects homozygous for the T allele. An increasing effect of the PPARD + 294 C allele was shown on serum LDL-C levels in nondiabetic CHD patients. In addition, the results suggested that the + 294 C allele might be associated with an increased LVH risk especially in male CHD patients. Furthermore, gene-gene interaction between the PPARD + 294T/C and the APOE polymorphisms was observed regarding LDL-C concentrations.
Keywords: APOLIPOPROTEIN-E POLYMORPHISM; ACTIVATED-RECEPTOR-ALPHA; SKELETAL-MUSCLE; ARTERY-DISEASE; RISK-FACTORS; E GENOTYPE; GAMMA; ATHEROSCLEROSIS; EXPRESSION; ASSOCIATION